급성 신부전으로 내원하여 진단된 방광의 부신경절종 1예 - 서인석; In Seok Seo; 남양훈; Yang Hoon Nam; 임지환; Ji Hwan Lim; 최준혁; Jun Hyuk Choi; 김장언; Jang Eon Kim; 최진호; Jin Ho Choi; et al. (Kidney research and clinical practice, 2007)
Pheochromocytoma is a catecholamines secreting tumor that usually appears in the adrenal medulla, sympathetic ganglia and extra-adrenal chromaffin tissue. About 10% of this disease is detected in the extra-adrenal chromaffin tissue which is called paraganglioma. The three major clinical symptoms of pheochromocytoma are headache, syncope and hypertension. Approximately 0.1% of hypertensive patients have pheochromocytoma. The extra-adrenal paraganglioma is found in abdominal sympathetic nerve ganglion or Zukerkandle`s organ with great frequency, but it also appears, albeit rare, in the cervical ganglion, thoracic cavity, bladder, and pelvic cavity. Some cases of paraganglioma in bladder are being reported internationally, but domestic reports are rare. We report a case of paraganglioma originating in the urinary bladder of patient who visited with acute renal failure associated with malignant hypertension. We treated him with phenoxybenzamine and later with partial cystectomy. High blood pressure was well controlled and acute renal failure was resolved.